Agromorphological and biochemical diversity of sea buckthorn in Northern Kazakhstan for breeding and conservation - GAUHAR S. MUKAN; LAURA SH. SHADMANOVA; AINUR S. YESZHANOVA; CHINGIZ B. KANAPIN; KANAT ZH. ACHATOV; MEDEU R. RAZHANOV; ANAR G. SANKAIBAYEVA; MARZHAN M. BAIMAGANBETOVA; GULNARA T. SITPAYEVA (Biodiversitas Journal of Biological Diversity, 2026)
Abstract. Mukan GS, Shadmanova LS, Yeszhanova AS, Kanapin CB, Achatov KZ, Razhanov MR, Sankaibayeva AG, Marzhan BM, Sitpayeva GT. 2026. Agromorphological and biochemical diversity of sea buckthorn in Northern Kazakhstan for breeding and conservation. Biodiversitas 27 (1): d270126. https://doi.org/10.13057/biodiv/d270126. Sea buckthorn (Hippophae rhamnoides), a versatile, dioecious shrub native to Eurasia, exhibits significant ecological and nutritional potential, yet remains underexploited in Kazakhstan despite widespread global utilization. This study evaluated the agromorphological and biochemical diversity of 11 selected forms (as proxies for potential genetic units) from five natural cenopopulations in the North Kazakhstan and Kostanay regions during 2023-2024 to identify elite forms suitable for breeding and commercial production. Field and laboratory assessments analyzed dendrometric, agromorphological, and biochemical traits. Dendrometric measurements revealed variations in bush height (2-4 m) and fruit cluster length (5.55-38.23 cm). Agromorphological fruit traits showed diversity in weight (24.36-48.47 g per 100 berries) and fruiting degree (2-5 points). Biochemical analyses indicated ranges in soluble solids (7.9-12.8%), sugars (1.2-7.5 g/100 g), polyphenols (401-1860 mg GAE/100 g), vitamin C (9.68-105.6 mg/100 g), and antioxidant activity (FRAP: 1.33-10.22 μM FeSO₄/g; DPPH: 18-78%). Cluster analysis identified the KT form as distinct, with superior antioxidant capacity. These findings highlight putative phenotypic divergence in underexplored northern populations, offering valuable resources for developing high-yielding, disease-resistant varieties adapted to harsh climates. The results support strategic breeding programs and advocate for the targeted conservation of unique forms (e.g., KT) to enhance agricultural and ecological resilience in the region.